TECHNICAL AND ECONOMIC EFFICIENCY ESTIMATION OF TRADITIONAL FISHERY BOATS, AT HODEIDA PROVINCE, REPUBLIC OF YEMEN - S. H. Al Kahtani; A. M. Elhendy; O. M. Al Eriani (Journal of Animal and Plant Sciences, 2015)
Estimating technical and economic efficiency, of traditional fishery sector, are considered as study objectives. Study results support fishing policy makers to adopt policies, which optimize the fishing resource use. In addition to save natural stock of fish, and determine the number fishing efforts, which satisfy the Maximum Sustainable Yield (MSY) of fish. Primary data collected by personal interviews with traditional fishermen at Republic Of Yemen, Hodeida Province, at fishing seasons in 2012 and 2013, are the main source of study data, in addition to the secondary data .The Data Envelopment Analysis (DEA) approach used for estimating technical and economic efficiency, based on fishing methods ( Hocks and Gill Nets), engine horsepower, and fishing boat sizes. Small boats, using Hocks fishing method and 60 horsepower engines, were technically less efficient than that for small boats using 40 horsepower engine. The first one can increase its yield by 14%, while the second one by only 9% using the same fishing resources. Large boats using 60 horsepower engine, and Gill Net fishing method, were more technically efficient than that for large boats using 40 horsepower engine. Small boats, using Hock fishing method, would increase its economic efficiency from 73% to 95% by increasing its engine horsepower from 60 to 70. While, large boats using Hocks get the highest economic efficiency, 84%, using 60 horsepower engine. Large boats using Gill Net fishing method can reduce costs by 7% of fishing costs and achieve the same level of production.
Keywords: Traditional fishery; Efficiency; constant return to scale; Data Envelopment Analysis